The influence of students’ engagement in mathematical problem solving activities - Salami, Olajumoke Olayemi; Spangenberg, Erica Dorethea (Interdisciplinary journal of education research, 2025)
The ability to retain and sustain students’ engagement in mathematics is crucial for fostering a lifelong interest in a subject that often turns students off. Problem-solving techniques are dynamic, particularly when integrated into teaching and learning in mathematics. This study evaluated how engaging students in mathematical problem-solving activities influenced their performance and learning outcomes in the subject. To achieve the set objectives, three hundred grade-eight students from twelve schools across Abuja, Nigeria, were sampled and analysed. The analyses included descriptive statistics, factor analysis for grouping problem-solving activities into distinct categories, and Pearson's correlation coefficient. The results showed that increased engagement in research-based problem-solving activities correlated with enhanced student performance across three key areas of achievement: knowledge, comprehension, and application. Therefore, the study recommends that students should be equipped with activities, facilities, and opportunities that will enhance their problem-solving skills in mathematics.